2016
DOI: 10.1017/s1368980016002172
|View full text |Cite
|
Sign up to set email alerts
|

Rice consumption, incidence of chronic diseases and risk of mortality: meta-analysis of cohort studies

Abstract: Objective: Findings from cohort studies investigating the association between rice consumption and risk of chronic diseases or mortality have been inconsistent. We performed a comprehensive systematic review and meta-analysis on all published cohort studies examining white rice consumption in relation to incidence of chronic diseases or risk of mortality. Design: A systematic literature search of MEDLINE, Embase, Cochrane review, Google Scholar and Scopus databases for relevant cohort studies published until J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…We found meta-analyses on the following exposures: healthy dietary pattern,23 unhealthy dietary pattern,24 HEI,25 alternative HEI (AHEI),25 DASH,25 Mediterranean diet,26 vegetarian diet,27 low carbohydrate diet,28 breakfast skipping,29 high glycaemic index,30 high glycaemic load,30 dietary acid load,31 dairy11 and dairy products,32 33 34 chocolate,35 eggs,11 meat36 and specific types of meat,36 37 38 39 total fish or seafood11 40 and types of fish,40 butter,41 olive oil,42 potatoes and types of potatoes,43 whole grain11 and whole grain products,44 refined grain,11 rice,45 white rice,44 brown rice,44 soy products,46 legumes,11 nuts,11 fruit and vegetables,47 total fruit11 and specific types of fruit,48 49 50 total vegetables11 and specific types of vegetables,51 52 tea,53 coffee,54 55 sugar sweetened beverages,56 artificially sweetened beverages,56 total fruit juice56 and types of fruit juice,57 total protein and types of protein,58 animal protein-to-potassium ratio,31 total fat,59 types of fat59 and fatty acids,59 60 61 62 dietary cholesterol,63 carbohydrates59 and types of carbohydrates,59 64 total fibre65 and types of fibre,65 vitamin D,66 niacin,67 iron,68 magnesium,69 calcium,70 selenium,71 polyphenols and subgroups of po...…”
Section: Resultsmentioning
confidence: 99%
“…We found meta-analyses on the following exposures: healthy dietary pattern,23 unhealthy dietary pattern,24 HEI,25 alternative HEI (AHEI),25 DASH,25 Mediterranean diet,26 vegetarian diet,27 low carbohydrate diet,28 breakfast skipping,29 high glycaemic index,30 high glycaemic load,30 dietary acid load,31 dairy11 and dairy products,32 33 34 chocolate,35 eggs,11 meat36 and specific types of meat,36 37 38 39 total fish or seafood11 40 and types of fish,40 butter,41 olive oil,42 potatoes and types of potatoes,43 whole grain11 and whole grain products,44 refined grain,11 rice,45 white rice,44 brown rice,44 soy products,46 legumes,11 nuts,11 fruit and vegetables,47 total fruit11 and specific types of fruit,48 49 50 total vegetables11 and specific types of vegetables,51 52 tea,53 coffee,54 55 sugar sweetened beverages,56 artificially sweetened beverages,56 total fruit juice56 and types of fruit juice,57 total protein and types of protein,58 animal protein-to-potassium ratio,31 total fat,59 types of fat59 and fatty acids,59 60 61 62 dietary cholesterol,63 carbohydrates59 and types of carbohydrates,59 64 total fibre65 and types of fibre,65 vitamin D,66 niacin,67 iron,68 magnesium,69 calcium,70 selenium,71 polyphenols and subgroups of po...…”
Section: Resultsmentioning
confidence: 99%
“…The process of dehulling and milling discards most micronutrients, fatty acids, anti-oxidants, and fiber. As a result, diets over-reliant on white rice risk deficiencies for several nutritional factors (Verma and Shukla, 2011;Sharma et al, 2013;Saneei et al, 2016;Sarma et al, 2018). The focus of rice breeding has long been concentrated on improving the crop's productivity, although some emphasis has been given to improving the size, shape, and amylose content of the grain (Breseghello, 2013;Rao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 3011 studies were reviewed from the search shown in Supplementary Table 1. After detailed review of relevant studies, a total of 16 reviews 7,1428 were included for all-cause mortality and 17 reviews 7,8,14,1720,22,2432 for CVD (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Average quality assessment score for CVD was 7.7/9 and all-cause death 7.9/9. Saneei 2017 15 Rice Hu et al score (out of 15).…”
Section: Supplementarymentioning
confidence: 99%